MiR-378a-3p and miR-491-5p as markers of xenon abuse in doping control - P. V. Postnikov; Z. G. Ordzhonikidze; R. A. Khanferyan; Yu. A. Efimova; I. V. Pronina (National Electronic Information Consortium (NEICON), 2024)
Xenon stimulates the synthesis of the hormone erythropoietin, which leads to improved oxygen supply to tissues, increased endurance and can be used by athletes to gain an undue advantage in competitions. The World Anti-Doping Agency (WADA) banned its use. The determination of xenon in biological fluids, in particular, in blood plasma samples, is difficult due to the narrow detection window. Its indirect detection is possible by changing in some blood parameters during a clinical analysis (RET%, HGB, HCT, etc.), however, this analysis is nonspecific and the use of other erythropoiesis-stimulating agents can lead to similar changes.Aims: The aim of the study was to search for long-term microRNA markers, the expression of which is specific and markedly altered by inhaled xenon.Methods: Quantitative real-time PCR was performed on CFX96 Bio-Rad analyser using miRCURY® LNA® miRNA SYBR® Green PCR Kit and panels for studying the expression profiles of mature microRNAs of the hypoxia signaling pathway miRCURY LNA™ miRNA Focus Panel.Results: Based on statistical data analysis, it was found that the expression of hsa-miR-378a-3p and hsa-miR-491-5p in blood plasma increases significantly (more than 70 times) when xenon inhalations are used as an erythropoiesis stimulator. Measurement of hematological parameters before and after inhalation showed no significant changes that could affect endurance or give competitive advantages.Conclusion: The evaluated difference in microRNA expression levels before and after administration of the xenon mixture (Xe/O2) makes hsa-miR-378a-3p and hsa-miR-491-5p potential candidates for the role of long-term markers of xenon abuse.